Surgical simulation - Dasgupta, Prokar; Ahmed, Kamran, 1977-; Jaye, Peter, 1967-; Khan, Mohammed Shamim; Cambridge eBooks (London : Anthem Press, 2014)
Now widely recognized as one of the most effective methods for training future surgeons, simulation has become an integral part of the multidimensional landscape that makes up a surgical education curriculum. This book provides an overview of the current status of simulation-based training in various surgical disciplines and explains the science of surgical education, from developing a simulation programme to properly assess surgeons-in-training, to transferring the skills acquired through simulation into real-life settings. As such, the book can be used as a guide for understanding the basics of surgical education.
Surgical simulation : an overview -- Simulation in historical perspective : the history of medical and surgical simulation -- The role of animal models in surgical training and assessment -- Full procedural surgical simulation -- Developing non-technical skills -- Learning curves for simulators -- Developing a simulation programme -- Patient safety and simulation -- Psychometrics -- Future of surgical simulation.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Surgery -- Computer simulation; Electronic books